Paternity fraud and compensation for misattributed paternity. Issue 8 (30th July 2007) - Draper, Heather
Abstract : Claims for reimbursement of child support, the reversal of property settlements and compensation can arise when misattributed paternity is discovered. The ethical justifications for such claims seem to be related to the financial cost of bringing up children, the absence of choice about taking on these expenses, the hard work involved in child rearing, the emotional attachments that are formed with children, the obligation of women to make truthful claims about paternity, and the deception involved in infidelity. In this paper it is argued that there should not be compensation for infidelity and that reimbursement is appropriate where the claimant has made child support payments but has not taken on the social role of father. Where the claimant's behaviour suggests a social view of fatherhood, on the other hand, claims for compensation are less coherent. Where the genetic model of fatherhood dominates, the "other" man (the woman's lover and progenitor of the children) might also have a claim for the loss of the benefits of fatherhood. It is concluded that claims for reimbursement and compensation in cases of misattributed paternity produce the same distorted and thin view of what it means to be a father that paternity testing assumes, and underscores a trend that is not in the interests of children.